1986
DOI: 10.1038/323411a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and expression of complementary DNA encoding the muscarinic acetylcholine receptor

Abstract: Cloning and sequence analysis of DNA complementary to porcine cerebral messenger RNA encoding the muscarinic acetylcholine receptor predict the complete amino-acid sequence of this protein. Expression of the complementary DNA produced functional muscarinic receptor in Xenopus oocytes. The muscarinic receptor is homologous with the beta-adrenergic receptor and rhodopsin in both amino-acid sequence and suggested transmembrane topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
254
2
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 884 publications
(263 citation statements)
references
References 56 publications
5
254
2
2
Order By: Relevance
“…22,23 Acetylcholine is stored in vesicles and is released by parasympathetic stimulation, activating primarily postsynaptic muscarinic and preganglionic nicotinic receptors. 24,25 The effects are terminated by rapid degradation by acetylcholinerases. 26 Increased parasympathetic stimulation decreases heart rate by decreasing SA node discharge rate and AV node conduction velocity.…”
Section: Effects Of the Sympathetic Nervous System On The Normal Myocmentioning
confidence: 99%
“…22,23 Acetylcholine is stored in vesicles and is released by parasympathetic stimulation, activating primarily postsynaptic muscarinic and preganglionic nicotinic receptors. 24,25 The effects are terminated by rapid degradation by acetylcholinerases. 26 Increased parasympathetic stimulation decreases heart rate by decreasing SA node discharge rate and AV node conduction velocity.…”
Section: Effects Of the Sympathetic Nervous System On The Normal Myocmentioning
confidence: 99%
“…Muscarinic cholinergic receptors belong to the superfamily of G-protein coupled receptors [42][43][44] that either activate or inhibit message transduction systems, thus having an effect on the intracellular second messengers such as cyclic AMP (cAMP) or inositol triphosphate (IP 3 ). Muscarinic receptors consist of seven transmembrane-spanning domains and are composed of 460-590 amino acids.…”
Section: Muscarinic Receptorsmentioning
confidence: 99%
“…Expression in Xenopus oocytes of cloned DNAs encoding four individual mAChR subtypes has revealed that mAChR I and mAChR III mediate activation of a Ca2+-dependent C1-current, whereas mAChR II and mAChR IV principally induce activation of Na ÷ and K ÷ currents in a Ca2+-independent manner [2][3][4]. Expression studies in mammalian cells have further shown that mAChR I and mAChR III are coupled efficiently with phosphoinositide hydrolysis [5][6][7], intracellular Ca 2÷ release [8], ac- Abbreviations: mAChR, muscarinic acetylcholine receptor; ACh, acetylcholine; NMS, N-methylscopolamine; QNB, quinuclidinyl benzilate tivation of Ca2+-dependent K ÷ currents [5,8,9] and inhibition of the M-current [5,8], whereas mAChR II and mAChR IV are linked preferentially with adenylate cyclase inhibition [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…The antagonist binding properties of individual mAChR subtypes expressed in Xenopus oocytes [2,3,12] show that mAChR I, mAChR II and mAChR III correspond most closely to the pharmacologically defined M1 (I), M2 cardiac (II) and M2 glandular (III) subtypes [13][14][15], respectively. This, together with the differential tissue distribution of the mRNAs encoding the individual mAChR species [2,[16][17][18][19], indicates that the mAChR heterogeneity in tissues with respect to antagonist binding is attributable to the presence of distinct mAChR gene products by themselves or in various combinations.…”
Section: Introductionmentioning
confidence: 99%